Evaluation of Public Service Quality: Between Regulation and Reality - Ita Ulansari; Mufarrihul Hazin; Ima Widiyanah; Budi Purwoko (Universitas Teuku Umar, 2025)
In the context of sustainable development (Sustainable Development Goals/SDGs), improving the quality of public services is an important aspect to support Goal 16,